Improving Pattern Recognition Skills of Children Aged 5-6 Years through Thematic Pattern Board Play - Pungky Puspita Sari; Nurul Kusuma Dewi (Universitas Sebelas Maret, 2026)
The purpose of this study was to improve the pattern recognition abilities of 5-6 year old children through playing with themed pattern boards at a kindergarten in Surakarta. This study used a classroom action research (CAR) approach based on Dave Ebbut's CAR model. The research subjects were 22 children aged 5-6 years. Data collection techniques in this study included performance tests, observation, interviews, and documentation. The data analysis techniques used were quantitative data analysis techniques with a comparative descriptive model and qualitative data analysis techniques with an interactive Miles and Huberman model. The results of this action research showed that there was an increase in the indicator of pattern recognition ability in 5-6-year-old children through playing with themed pattern boards. The pre-action data showed that 31.82% of children completed the test, increasing in cycle 1 with 48.48% of children completing the test, and increasing in cycle 2 with 60.60% of children completing the test, and increasing again in cycle 3 with 74.24% of children completing the test. Pattern recognition ability of children aged 5-6 years can be improved through playing themed pattern boards and can achieve a minimum completion target of 70%.